Development of a simple mechanical measurement method to measure spasticity based on an analysis of a clinical maneuver and its concurrent validity with the modified Ashworth scale - Tanikawa, Hiroki; Mukaino, Masahiko; Itoh, Shota; Kondoh, Hikaru; Fujimura, Kenta; Teranishi, Toshio; Ohtsuka, Kei; Hirano, Satoshi; Kagaya, Hitoshi; Saitoh, Eiichi; Otaka, Yohei (Frontiers in Bioengineering and Biotechnology, 2022)
Background Despite recent developments in the methodology for measuring spasticity, the discriminative capacity of clinically diagnosed spasticity has not been well established. This study aimed to develop a simple device for measuring velocity-dependent spasticity with improved discriminative capacity based on an analysis of clinical maneuver and to examine its reliability and validity. Methods This study consisted of three experiments. First, to determine the appropriate motion of a mechanical device for the measurement of velocity-dependent spasticity, the movement pattern and the angular velocity used by clinicians to evaluate velocity-dependent spasticity were investigated. Analysis of the procedures performed by six physical therapists to evaluate spasticity were conducted using an electrogoniometer. Second, a device for measuring the resistance force against ankle dorsiflexion was developed based on the results of the first experiment. Additionally, preliminary testing of validity, as compared to that of the Modified Ashworth Scale (MAS), was conducted on 17 healthy participants and 10 patients who had stroke with spasticity. Third, the reliability of the measurement and the concurrent validity of mechanical measurement in the best ankle velocity setting were further tested in a larger sample comprising 24 healthy participants and 32 patients with stroke. Results The average angular velocity used by physical therapists to assess spasticity was 268 ± 77 °/s. A device that enabled the measurement of resistance force at velocities of 300 °/s, 150 °/s, 100 °/s, and 5 °/s was developed. In the measurement, an angular velocity of 300 °/s was found to best distinguish patients with spasticity (MAS of 1+ and 2) from healthy individuals. A measurement of 300 °/s in the larger sample differentiated the control group from the MAS 1, 1+, and 2 subgroups (p <0.01), as well as the MAS 1 and 2 subgroups (p <0.05). No fixed or proportional bias was observed in repeated measurements. Conclusions A simple mechanical measurement methodology was developed based on the analysis of the clinical maneuver for measuring spasticity and was shown to be valid in differentiating the existence and extent of spasticity. This study suggest possible requirements to improve the quality of the mechanical measurement of spasticity.